Disentangling environmental drivers of metabolic flexibility in birds: the importance of temperature extremes versus temperature variability. Issue 8 (16th November 2015) - Stager, Maria; Pollock, Henry S.; Benham, Phred M.; Sly, Nicholas D.; Brawn, Jeffrey D.; Cheviron, Zachary A.
Abstract : Examining physiological traits across large spatial scales can shed light on the environmental factors driving physiological variation. For endotherms, flexibility in aerobic metabolism is especially important for coping with thermally challenging environments and recent research has shown that aerobic metabolic scope [the difference between maximum thermogenic capacity (Msum ) and basal metabolic rate (BMR)] increases with latitude in mammals. One explanation for this pattern is the climatic variability hypothesis, which predicts that flexibility in aerobic metabolism should increase as a function of local temperature variability. An alternative explanation is the cold adaptation hypothesis, which predicts that cold temperature extremes may also be an important driver of variation in metabolic scope. To determine the thermal drivers of aerobic metabolic flexibility in birds, we combined data on metabolic scope from 40 bird species sampled across a range of environments with several indices of local ambient temperature. Using phylogenetically‐informed analyses, we found that minimum winter temperature was the best predictor of variation in avian metabolic scope, outperforming all other thermal variables. Additionally, Msum was a better predictor of latitudinal patterns of metabolic scope than BMR, with species inhabiting colder environments exhibiting increased Msum over their counterparts in warmer environments. Taken together, these results suggest that cold temperature extremes drive latitudinal patterns of metabolic scope via selection for enhanced thermogenic performance in cold environments, supporting the cold adaptation hypothesis. Temperature extremes may therefore be an important selective pressure driving macrophysiological trends of aerobic performance in endotherms.